THEORETICAL MODEL OF INTELLECTUAL CAPITAL FOR THE REVERSE LOGISTICS POST-SALE PROCESS: Case of Refrigeration Appliances - Vaz, Caroline Rodrigues; Grabot, Bernard; Houé, Raymond; Maldonado, Mauricio Uriona; Selig, Paulo Mauricio; Taboada Rodriguez, Carlos Manoel (Perspectivas Contemporâneas, 2015)
This article aims to present a theoretical conceptual model of intellectual capital for the process of reverse logistics of refrigeration appliances. In this way, the research hypothesis is: Isn´t there significant influence of intellectual capital in all these stages of reverse logistics aftermarket refrigerators? In this context, this research offers a systematic analysis of the literature for the development of the constructs, variables and measurable indicators, based on the method Proknow-C. A literature review was performed on four databases from CAPES in 2012 and found3748 articles, after the filtering process 73 articles remained for content analysis, from which the constructs and variables were extracted to form the theoretical model. The constructs and variables of Intellectual Capital are: Human Capital subdivided into Skills, Relational Capital in Customer Relationship Intensity and Market and Structural Capital on Organizational Structure, Process and Operational System Information. And for Reverse Logistics are: Operating Process Efficiency, Quality Process and Legislation. For each construct and its variables measurable indicators were established. Eigth indicators were established for Human Capital, nine for Structural Capital, six for Relational Capital and fourteen for Reverse Logistics post-sale. This theoretical conceptual model is applied to refrigeration appliances due to large amount of waste discarded and major environmental problems caused by having chemicals and toxic gases inside it that act directly on the greenhouse effect. Therefore, to occur all these aspects the organization needs to enhance the skills of intellectual capital in their activities to provide a more efficient process, and adding value, even increase the competitive advantage of the company to the market. MODELO TEÓRICO DE CAPITAL INTELECTUAL PARA O PROCESSO DE LOGÍSTICA REVERSA DE PÓS-VENDA: Caso de Aplicação em Refrigeradores Este artigo tem como objetivo apresentar um modelo teórico conceitual de capital intelectual no processo de logística reversa de pós-venda de refrigeradores. A fim de responder a hipótese da pesquisa: há influência significativa do capital intelectual em todas essas etapas do processo de logística reversa de pós-venda de refrigeradores? Esta pesquisa trata de uma análise sistemática de revisão de literatura para construção dos constructos, variáveis e indicadores mensuráveis, com base no método Proknow-C. A revisão de literatura foi realizada em quatro bases de dados do portal da CAPES em 2012, encontrando 3748 artigos, realizado as filtragens pelo método aplicado, restaram para análise de conteúdo 73 artigos, os quais foram analisados e retirados os constructos e variáveis para o modelo teórico. Os constructos e variáveis encontrados para Capital Intelectual foram: Capital Humano subdividido em Competências, Capital Relacional em Relação com o Cliente e a Intensidade de Mercado, e Capital Estrutural em Estrutura Organizacional, Processo Operacional e Sistema de Informação. E para Logística Reversa foram: a Eficiência do Processo Operacional, Qualidade do Processo e Legislação. Para cada constructo e suas variáveis foram estabelecidos indicadores mensuráveis e apresentando uma definição própria a respeito de cada um dos elementos. Para Capital Humano foram estabelecidos oito indicadores, o Capital Estrutural em nove, o Capital Relacional em seis e a Logística Reversa de pós-venda em 14 indicadores mensuráveis. O processo de logística reversa de pós-venda baseado para a aplicação deste modelo teórico conceitual é o dos refrigeradores, devido a grande quantidade destes resíduos descartados e aos grandes problemas ambientais causados, por possuírem componentes químicos e tóxicos, no seu interior que atuam diretamente no efeito estufa. Portanto, para que ocorram todos esses aspectos a organização precisa potencializar as competências do capital intelectual em suas atividades para proporcionar uma maior eficiência no processo, além de agregação de valor, até mesmo aumentar a vantagem competitiva da empresa ao mercado.